Digital Literacy as a Tool for Community Empowerment in Undeveloped and Peripheral Areas - Nursalim, Nursalim; Witdianti, Yeni; Marzuki, Ismail; Rangkoly, Santji Afi (Journal Ligundi of Community Service, 2026)
Background. Digital inequality remains a persistent barrier to social and economic development in undeveloped and peripheral areas, limiting communities’ access to information, public services, and economic opportunities. While infrastructure gaps are often emphasized, insufficient digital literacy frequently becomes a more decisive constraint on meaningful participation in the digital ecosystem. Purpose. This study aims to examine digital literacy as a strategic tool for community empowerment, focusing on how digital competencies can enhance social participation, economic resilience, and local capacity building in underserved and peripheral contexts. Method. This research employs a mixed-methods approach combining a community-based survey with in-depth interviews involving residents, local facilitators, and community leaders in selected peripheral areas. Quantitative data were analyzed descriptively and inferentially to identify patterns of digital skill acquisition and usage, while qualitative data were thematically analyzed to capture contextual experiences, challenges, and empowerment outcomes. Results. The findings indicate that digital literacy interventions significantly improve community members’ ability to access information, utilize digital public services, and engage in microeconomic activities such as online marketing and digital financial services. However, the impact varies depending on age, educational background, and local support systems. Communities with participatory training models and contextualized learning materials demonstrate higher levels of digital confidence, collective problem-solving, and sustainable technology adoption. Conclusion. Digital literacy functions not merely as a technical skill but as a catalyst for broader community empowerment in undeveloped and peripheral areas. Effective digital literacy programs must be context-sensitive, inclusive, and community-driven to ensure long-term empowerment rather than short-term technological exposure. This study contributes to the discourse on digital inclusion by emphasizing literacy-oriented approaches as a foundation for equitable development.